Penerapan Metode Tabarak dalam Meningkatkan Efektivitas Hafalan Al-Qur’an Santri di Rumah Tahfidz Mihrobul Quran - Hallim Kesuma, Friatma; Juriono, Juriono; Irwansyah, Irwansyah (Jurnal Ilmu Pendidikan Islam, 2024)
This study aims to examine the application of the Tabarak method in improving early childhood Al-Qur'an memorization at the Mihrobul Quran Tahfidz House, Bengkel Village. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the Tabarak method is effective in forming children's memorization patterns in a gradual, structured, and enjoyable manner. The success of this method is supported by supporting factors such as the availability of adequate facilities and infrastructure, discipline, regular eating and sleeping patterns, active involvement of parents, and the provision of motivation in the form of rewards. However, the study also found several obstacles such as the lack of focus of children when listening to murottal, lateness, absence, and minimal supervision of memorization at home. These findings confirm that the success of the Tabarak method is highly dependent on the synergy between institutions, teachers, and parents in creating an environment that supports the habituation of the Al-Qur'an from an early age.